Thrombosed great saphenous vein aneurysm accompanied by venous thrombosis - Rendón Elías, Felipe Gerardo; Albores Figueroa, Rosemberg; Arrazolo Ortega, L. S.; Torres Alcalá, F.; Hernández Sánchez, Marely; Gómez Danés, Luis Humberto (UANL. Facultad de Medicina, 2015)
Superficial venous aneurysms of the lower extremities are considered rare and their clinical significance is poorly defined. The purpose of this article is to report a case of a 72- year-old woman with a thrombosed great saphenous vein aneurysm along with deep venous thrombosis and review its clinical presentation, diagnosis and treatment.